STRATEGI KEPEMIMPINAN KIAI DALAM MEMBENTUK KEDISIPLINAN SANTRI DI PONDOK PESANTREN - Arina Tazkiatan Nufus; Muh. Hanif (STAI DI AL-HIKMAH, 2026)
This study examines the leadership strategies employed by a kiai in fostering student discipline at Jogonegoro Islamic Boarding School (Pondok Pesantren Jogonegoro). Using a qualitative field research approach, data were collected through participant observation, in-depth interviews with the kiai, boarding school administrators, and students (santri), as well as documentation analysis. The findings reveal three primary leadership strategies: (1) direct role modeling (uswah hasanah) through the kiai’s consistent presence in leading congregational prayers and religious study sessions; (2) the internalization of disciplinary values through verbal guidance delivered in religious gatherings, where discipline is framed as a spiritual obligation and an essential aspect of the ethics of seeking knowledge; and (3) a gradual mentoring system implemented by administrators through dialogue, warnings, and reporting serious violations to the kiai. The study further finds that students initially comply with regulations out of fear of punishment (ta'zir), but gradually develop voluntary obedience driven by respect and reverence for the kiai’s authority. Nevertheless, challenges remain, particularly in maintaining consistent discipline in daily routines such as the dawn (Fajr) prayer, where physical fatigue and demanding schedules tend to reduce compliance. This study contributes to the sociology of Islamic education by highlighting how charismatic religious authority, when combined with systematic structural supervision, produces a distinctive model of discipline formation within the pesantren environment.